Predictors of Cervical Cancer Screening Uptake among Healthcare Providers in Siaya County, Kenya - Zilper Imbuye; Damaris Ochanda; John Arudo (Evidence-Based Nursing Research)
Context: Cervical cancer ranks as the second most frequent cancer among women in Kenya and the second most frequent cancer among women between 15 and 44 years of age. Cases of cervical cancer among health professionals have equally been on the rise.